1991
DOI: 10.1029/91jb01574
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependent electrical properties of polycrystalline olivine compacts

Abstract: The complex electrical properties of poly crystalline San Carlos olivine compacts were measured over the range of frequency l0−4–104Hz from 800° to 1400°C under controlled oxygen fugacity. The impedance data display a strong frequency dependence that is evidenced most clearly when the results are displayed in the complex impedance plane. A parameterized model of the frequency dependent electrical response using equivalent electrical circuits is presented. Two distinct conduction mechanisms of the sample are ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
2
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 45 publications
(26 reference statements)
8
97
2
1
Order By: Relevance
“…This observation remains controversial, however, as other workers have measured conductivities on single crystals and samples with a range of grain sizes and have not seen any systematic variation in conductivity with grain size (Roberts and Tyburczy, 1991;Xu et al, 2000b;Wang et al, 2006 Boyd, 1987). In addition, Li et al (2005) analysed grain interior and grain boundary conduction in pyroxenes, and found that grain-boundary conduction is important at high frequencies, above 100 Hz.…”
Section: Effect Of Grain Sizementioning
confidence: 81%
“…This observation remains controversial, however, as other workers have measured conductivities on single crystals and samples with a range of grain sizes and have not seen any systematic variation in conductivity with grain size (Roberts and Tyburczy, 1991;Xu et al, 2000b;Wang et al, 2006 Boyd, 1987). In addition, Li et al (2005) analysed grain interior and grain boundary conduction in pyroxenes, and found that grain-boundary conduction is important at high frequencies, above 100 Hz.…”
Section: Effect Of Grain Sizementioning
confidence: 81%
“…The values of imaginary parts almost remain unchanged within a frequency range of 10 6 -10 5 Hz, and the values gradually increased at 10 5 -10 3 Hz and decreased at 10 3 -10 1 Hz; these values then slowly increased in the 10 1 to 10 −1 Hz lower-frequency region. Roberts and Tyburczy (1991) and Saltas et al (2013) have suggested that the ideal semicircle represents the bulk electrical properties of a sample, and the additional tail is characteristic of diffusion processes at the sample-electrode interface. Hence, the bulk sample resistance can be obtained by fitting the ideal semicircle in the high-frequency domain.…”
Section: Resultsmentioning
confidence: 99%
“…ROBERTS and TYBURCZY (1991) show that grain boundaries act in series with grain interior conduction and at the low frequencies of geomagnetic induction decrease conductivity by about a factor of 2 (one-third an order of magnitude), although the effect of pressure on the grain boundary conduction mechanism is completely unknown. However, the conductivity of a mantle lherzolite measured recently ,by DuBA and CONSTABLE (1993) varied between S02 and 0.15 orders of magnitude more conductive.…”
Section: Discussionmentioning
confidence: 99%